PERTUMBUHAN ISOLAT RHIZOBAKTERI PELARUT FOSFAT DARI TANAMAN PADI DI MAYONG, JEPARA PADA MEDIA LIMBAH RUMAH PEMOTONGAN HEWAN DAN AIR KELAPA - Rutty Wulandari; Agung Suprihadi; Budi Raharjo (Jurnal Akademika Biologi, 2013)
The farmers are now turning towards the use of biofertilizer. The biofertilizer is living microbes applied to the soil in order to help facilitate or provide certain nutrients for plants. Previous study found that B4 isolate has proven capable of solubilizing phosphate so that it could be used as an agent  that was inoculated in biofertilizer. The fertilizer can be formulated by modifying the alternative growth media in the liquid form that has potential, which is slaughterhouse waste and coconut water. Both  media contain organic matters which support the growth of bacteria. This study aimed to test the potential of slaughterhouse waste and coconut water as a medium for the growth of B4 isolate. Methods  of research conducted by Randomized Block Design, in which consists of five treatments namely P1 (100% coconut water), P2 (25% slaughterhouse waste & 75% coconut water), P3 (50% slaughterhouse waste & 50% coconut water), P4 (75% slaughterhouse waste & 25% coconut water), and P5 (100% slaughterhouse waste). The measured variable was the number of bacteria in the organic waste media during the 48 hours incubation period. Data on the number of bacteria was analysed by ANOVA  test  then  continued  with  Duncan  and  LSD  further  tests.  The  results  showed  that P4 treatment significantly different from other treatments, with the highest number of bacteria (1,9 x 1011CFU/mL) at 18 hours incubation. The density of bacterial population in the five formula medias every 3 hours during the 48 hours incubation period showed significantly different, except at 0, 3, 12, and 45 hours incubation. Key words: biofertilizer, phosphate, slaughterhouse waste, coconut water